Diversity of Fusarium associated banana wilt in northern Viet Nam - Le Thi, L.; Mertens, A.; Vu, D.T.; Vu, T.D.; Anh Minh, P.L.; Duc, H.N.; Backer, S. de; Swennen, Rony L.; Vandelook, F.; Panis, Bartholomeus; Amalfi, M.; Decock, C.; et al. (Pensoft Publishers, 2022)
Fusarium is one of the most important fungal genera of plant pathogens that affect the cultivation of a wide range of crops. Agricultural losses caused by Fusariumoxysporumf.sp.cubense (Foc) directly affect the income, subsistence, and nourishment of thousands of farmers worldwide. For Viet Nam, predictions on the impact of Foc for the future are dramatic, with an estimated loss in the banana production area of 8% within the next five years and up to 71% within the next 25 years. In the current study, we applied a combined morphological-molecular approach to assess the taxonomic identity and phylogenetic position of the different Foc isolates collected in northern Viet Nam. In addition, we aimed to estimate the proportion of the different Fusarium races infecting bananas in northern Viet Nam. The morphology of the isolates was investigated by growing the collected Fusarium isolates on four distinct nutritious media (PDA, SNA, CLA, and OMA). Molecular phylogenetic relationships were inferred by sequencing partial rpb1, rpb2, and tef1a genes and adding the obtained sequences into a phylogenetic framework. Molecular characterization shows that c. 74% of the Fusarium isolates obtained from infected banana pseudostem tissue belong to F.tardichlamydosporum. Compared to F.tardichlamydosporum, F.odoratissimum accounts for c.10% of the Fusarium wilt in northern Viet Nam, demonstrating that Foc TR4 is not yet a dominant strain in the region. Fusariumcugenangense – considered to cause Race 2 infections among bananas – is only found in c. 10% of the tissue material that was obtained from infected Vietnamese bananas. Additionally, one of the isolates cultured from diseased bananas was phylogenetically not positioned within the F.oxysporum species complex (FOSC), but in contrast, fell within the Fusariumfujikuroi species complex (FFSC). As a result, a possible new pathogen for bananas may have been found. Besides being present on several ABB ‘Tay banana’, F.tardichlamydosporum was also derived from infected tissue of a wild Musalutea, showing the importance of wild bananas as a possible sink for Foc.